Effects of sensory experiences on science literacy learning and retention - Vondriska, Emily (My University, 2013)
Our senses help shape how we behave and react to our environment. They also provide input about our environment and help us encode what we learn into our memory. Much of the knowledge that we receive through visual, oral, auditory, olfactory, and tactile/psychomotor processes provide a database for us that can be retrieved for later use or be integrated with our previous experience. The purpose of this research is to determine the effects of sensory experiences on cognition and memory retention in literacy. Knowledge obtained from this investigation can benefit those who find it difficult to gain thorough and in-depth knowledge of a topic, or to retain and recall information, especially in the area of life sciences. Many topics taught require spatial thinking: the ability to analyze, problem solve, and predict patterns. An individual has to develop the ability to imagine what a phenotype of a heterozygous pea plant might look like if it is dominant red. She may need to remember major arteries and veins and then be able to describe their path and what they carry. How do pupils understand and retain such information? One key component is developing several connections to a concept, and the second key is employing sensory experiences that support the recall of subject matter. Research has indicated that engaging our senses to learn and "see" a concept greatly enhances our ability to understand and retain what we have learned. Engaging our senses while learning results in the encoding of what we have experienced into something that can be processed, retrieved and recalled from our short and long-term memories. This study also aims to determine which sensory experience(s) can aid and cue for cognition and memory retention/recall and if an accumulation of sensory experiences further enhances learning and memory.
Plan B Paper. 2013. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. 65 leaves. Includes bibliographical references (leaves 30-32).